The effect of water content and nutrient on soil microbial behaviour - Ain Art Atiqah, Selamat (2015)
Palm oil mill effluent (POME) is one of the major wastes from palm oil mill industry and it has the problematic environmental pollution potential among the palm oil mill wastes. Mostly, factories in Malaysia have been existed since 70th century. In most cases, palm oil mill effluent was discharged in ponds near the mills. In the cases of ponds without proper liner system, POME will tend to seep into deep ground. If the inflitrated POME is not treated, it will inevitably pollute groundwater reservoir. The aim of this study was to demonstrate the optimum water content in which soil microbe can survive effectively to remove contaminants in contaminated soils. The sample of soil will be used in this research study is taken from palm oil mill plantation which is located in Tawau, Sabah. Two samples were prepared in different condition and there are soil-water mixture and soil-POME mixture. The both conditions of samples were prepared by mixing the air dried soil powders with deionised water and POME respectively at target water content equals to 1.2 times with the respective liquid limits of the test soils. Soil-water mixture and soil-POME mixture was placed in the desiccators with different suction pressure generated by different types of salt solutions. Both samples were placed in the desiccator until the stable water content reading were recorded. There are consists five types of salt solutions used in this test which are K2SO4, K2CO3, Nacl, KNO3 and KCl. The different salt solution generated different values of suction pressure and water contents. The suction pressure value of 10.58 Mpa is the most effective to generate the optimum water content corresponding to the least value of total nitrogen produced in soil-POME mixture sample. The reduction of total nitrogen in soil-POME mixture was decreased the initial value of total nitrogen from 4.5 mg/l to 0.4 mg/l after undergoing the treatment process through vapor equilibrium technique. The optimum water content for microbe to survive is the most effective at a water content of 83.5%. The identification of microorganisms was carried out by using the spread plating and an isolation plating technique. Two types of bacteria were successfully identified by the central laboratory and there are Trichoderma atroviridae and Paecilomyces lilacinus. The implication of these findings is that the bacteria found in soil can be useful in the rehabilitation of POME polluted soil and possibly other oil polluted sites.